Penerapan Model Problem Based Learning Terhadap Partisipasi Siswa Di Tinjau Dari Kompetensi Pedagogik Guru - Diva Dwi Riyadi; Babang Robandi (Jurnal Lensa Pendas, 2025)
This study aims to explore the implementation of the Problem-Based Learning (PBL) model in increasing student participation, as viewed from the pedagogical competence of teachers. Pedagogical competence is an essential element that determines the effectiveness of learning, including in the implementation of PBL, which requires the teacher’s ability to design, manage, and evaluate problem-based learning processes. This study uses a library research approach, referring to various academic literature such as books, scholarly journals, and relevant dissertations. Data were collected from various sources discussing learning strategies, research methodologies, and the implementation of PBL in the educational context. Data analysis was conducted using a content analysis approach, through the process of identifying patterns, themes, and relationships in the analyzed literature. The research findings indicate that good pedagogical competence allows teachers to create a collaborative learning environment, motivate students to think critically, and enhance their involvement in the learning process. Furthermore, effective implementation of PBL requires teachers’ skills in guiding students to solve problems independently, so that active student participation can be realized. This study concludes that improving teachers' pedagogical competence, especially in the context of PBL, has significant implications for the success of learning based on active participation. Therefore, teacher professional development through training and pedagogical competence development programs is an essential step to support the optimal implementation of PBL. This research is expected to serve as a reference for educators and policymakers in designing strategies to improve the quality of education through strengthening teachers' pedagogical competence.